The applied biochemistry of PEDF and implications for tissue homeostasis - Broadhead, M.; Becerra, S.; Choong, P.; Dass, Crispin (Informa Healthcare, 2010)
Pigment epithelium-derived factor (PEDF) is an endogenously produced glycoprotein with a spectrum of biological roles across diverse pathologies. Recent research has focused on the biochemical properties of PEDF and its associated receptors. This review discusses the recent developments in PEDF biochemistry and how this new knowledge will help progress our understanding of PEDF as a molecular mediator for anti-angiogenesis and-tumorigenesis. Additionally, pathophysiological roles for PEDF in healing and tissue homeostasis are being revealed and our enhanced understanding of the interactions between PEDF and its receptors may yet prove useful in propelling PEDF towards clinical application.